Characterization of anti-steatogenic long noncoding RNAs and their epigenetic influence on the development of metabolic fatty liver disease – a systematic review - Abaturov, Oleksandr; Nikulina, Anna (Rzeszów University Press, 2025)
Introduction and aim. Numerous transcriptomic studies have demonstrated that the development of metabolically associated fatty liver disease is accompanied by changes in the expression level of long noncoding RNAs (lncRs). The aim: to present a brief description of the role of anti-steatogenic lncRs in the epigenetic influence on the development of metabolically associated fatty liver disease, analyzing the data of modern scientific literature. Material and methods. An analysis of 64 reports over the past 10 years was conducted from the databases PubMed; MEDLINE; EMBASE; Cochrane Systematic Reviews Database; BIOSIS which were selected using the indicated keywords. Quality aspects were assessed using the adapted Newcastle–Ottawa Scale, PROSPERO CRD420250652980. Analysis of the literature. Hypoexpression of AC012668 – increased representation of miR-380-5p, activation of LRP2; B4GALT1- AS1/lncSHGL, MEG3 – activation of lipogenesis, gluconeogenesis in hepatocytes; FLRL2 – inhibition of BMAL1 and SIRT1; Gm16551 – increased expression of ACC1, SCD1; HR1 – activation of SREBP1c. LncLSTR – activation of cytochrome Cyp8b1 transcription; MRAK052686 reduction of FABP7 expression. Conclusion. The formation of hepatosteatosis is supported by a decrease in the expression level of anti-steatogenic lncRs, such as AC012668, B4GALT1-AS1/lncSHGL, MEG3, FLRL2, Gm16551, lncHR1, lncLSTR, MRAK052686. LncRs overexpression is compensatory in escalating inflammation, hyperglycemia.
Keywords: anti-steatogenic long noncoding RNAs; epigenetic regulation; metabolically associated fatty liver disease; obesity